T helper cell 17/regulatory T cell balance regulates ulcerative colitis and the therapeutic role of natural plant components: a review - Zhao, Da; Ge, Anqi; Yan, Cong; Liu, Xingci; Yang, Kailin; Yan, Yexing; Hao, Moujia; Chen, Junpeng; Daga, Pawan; Dai, Charles C.; Li, Changping; Cao, Hui (Frontiers in Medicine, 2025)
Ulcerative colitis (UC) is a chronic relapsing inflammatory disease characterized by progressive mucosal damage. The incidence rate of UC is rising rapidly, which makes the burden of medical resources aggravated. In UC, due to various pathogenic factors such as mucosal immune system disorders, gene mutations and environmental factors disrupting the mucosal barrier function, the midgut pathogenic bacteria and exogenous antigens translocate into the lamina propria, thereby aggravating the inflammatory response and further damages the mucosal barrier. During the progression of UC, Th17 populations that cause inflammation generally increase, while Tregs that suppress Th17 activity decrease. Among them, Th17 mediates immune response, Treg mediates immunosuppression, and the coordinated balance of the two plays a key role in the inflammation and immune process of UC. Natural plant components can regulate biological processes such as immune inflammation from multiple levels of proinflammatory cytokines and signaling pathways. These characteristics have unique advantages and broad prospects in the treatment of UC. In immunomodulation, there is substantial clinical and experimental evidence for the modulatory role of natural plant products in restoring balance between Th17/Treg disturbances in UC. This review summarizes the previous studies on the regulation of Th17/Treg balance in UC by natural plant active ingredients, extracts, and traditional Chinese medicine prescriptions, and provides new evidence for the development and design of lead compounds and natural new drugs for the regulation of Th17/Treg balance in the future, and then provides ideas and evidence for future clinical intervention in the treatment of UC immune disorders and clinical trials.